2012
DOI: 10.1016/j.cbpb.2011.12.004
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic analyses of intestinal gene expression of juvenile Atlantic cod (Gadus morhua) fed diets with Camelina oil as replacement for fish oil

Abstract: 20For aquaculture of marine species to continue to expand, dietary fish oil (FO) must be replaced 21 with more sustainable vegetable oil (VO) alternatives. Most VO are rich in n-6 polyunsaturated 22 fatty acids (PUFA) and few are rich in n-3 PUFA but Camelina oil (CO) is unique in that, besides 23 high 18:3n-3 and n-3/n-6 PUFA ratio, it also contains substantial long-chain monoenes, 24 commonly found in FO. Cod (initial weight ~1.4 g) were fed for 12 weeks diets in which FO was 25 replaced with CO. Growth perf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
51
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(57 citation statements)
references
References 63 publications
6
51
0
Order By: Relevance
“…Moreover, elongase 5 (elovl5) gene expression levels were not detected in all groups. In other studies in marine species, Atlantic cod and sea bass, replacement of fish oil by vegetable oil demonstrated no significant response in the expression and activity of elovl5 at the intestinal level (Morais et al, 2012;Castro et al, 2014), however, increased expression of elovl5 in the liver was observed in both species (Tocher et al, 2006;Castro et al, 2014).…”
Section: Tablementioning
confidence: 86%
“…Moreover, elongase 5 (elovl5) gene expression levels were not detected in all groups. In other studies in marine species, Atlantic cod and sea bass, replacement of fish oil by vegetable oil demonstrated no significant response in the expression and activity of elovl5 at the intestinal level (Morais et al, 2012;Castro et al, 2014), however, increased expression of elovl5 in the liver was observed in both species (Tocher et al, 2006;Castro et al, 2014).…”
Section: Tablementioning
confidence: 86%
“…In the US, several states are actively growing Camelina as a biofuels crop, indicating the wide acceptance of this crop platform. Furthermore, wild-type Camelina oil has already been shown to be suitable for inclusion in fish feeds and contains no anti-nutritional factors detrimental to fish growth (Petropoulos et al, 2009;Morais et al, 2012b;Hixson et al, 2014). Ultimately, all animal production will depend on terrestrial plants/agriculture and this requires land.…”
Section: Transgenicsmentioning
confidence: 99%
“…Studies have demonstrated that vegetable oil (either singly or as blends), which is high in C 18 PUFA such as 18:3ω3 and 18:2ω6 but devoid of the LC-PUFA, can be used to replace up to 100% of FO without negatively influencing growth in salmonids and marine fish (Bell et al, 2001Torstensen et al, 2005;Morais et al, 2012a;Hixson et al, 2013;Xue et al, 2014). However, the ω3 LC-PUFA content in fish fillets can be reduced significantly if FO is replaced by vegetable oil completely Morais et al, 2012a). Moreover, the expression of genes involved in the LC-PUFA biosynthetic pathway is known to be altered following vegetable oil dietary treatments.…”
Section: Introductionmentioning
confidence: 99%
“…CO-containing diets have been used in studies involving Atlantic cod (Gadus morhua) (Morais et al, 2012a;Hixson et al, 2013;Booman et al, 2014;Hixson and Parrish, 2014;Xue et al, 2014), Atlantic salmon Leaver et al, 2011;Morais et al, 2011b;Hixson et al, 2014b), and rainbow trout (Oncorhynchus mykiss) (Hixson et al, 2014a). Previously in Atlantic salmon, CO was included in blends (20% CO) with other plant-based oils to study the effect of substituting FO with vegetable oil blends on growth , ω3 LC-PUFA deposition in the flesh (Leaver et al, 2011), and cholesterol and lipoprotein metabolism (Morais et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%